Sustainability of healthcare system improvements, programmes and interventions in acute care settings: protocol for a mixed methods systematic review - Franz E Babl; Sandy Middleton; Julie Cowie; Catherine Wilson; Peter Wilson; Pauline Campbell; Emma Tavender; Lisa Kuhn; Nicola Straiton; Victoria Ramsden; Elizabeth McInnes (BMJ Open)
Introduction Sustaining evidence-based care is challenging in all clinical settings. Acute care settings have a unique set of contextual factors that may impact sustainability (eg, fast-paced, regular staff turnover). Much of the previous research explores sustainability across undifferentiated healthcare settings making it difficult to determine factors that influence sustainability in acute care settings. The aim of this review is to identify facilitators and barriers that influence the delivery of sustained healthcare interventions (eg, integration of clinical guidelines) within adult and paediatric hospital-based acute care settings.Methods and analysis A mixed methods systematic review updating Cowie et al’s (which included studies from 2008 to 2017) previously published systematic review will be conducted. The following databases will be searched: Medline, Embase, Cochrane Database of Systematic Reviews, CINAHL and Allied and Complementary Medicine (AMED), from November 2017 to the present for studies published in English. Relevant reference lists of included studies will be manually searched. Empirical quantitative and qualitative studies that report the sustainability of an intervention or programme in acute care settings using a theoretical framework(s), model(s) or theory(ies) to explore facilitators and barriers, will be included. Studies will be exported into Covidence (Melbourne) and pairs of reviewers will independently screen abstracts and full-text studies. The discussion will be used to resolve any disagreements and a third coauthor enlisted should a consensus not be reached. Two independent coauthors will extract key study characteristics and assess each study’s quality. Data will be extracted using Covidence (Melbourne). Evidence tables will be used to present descriptive data. Facilitators and barriers will be mapped to the Consolidated Framework for Sustainability Constructs in Healthcare and a narrative approach will be used to present key findings.Ethics and dissemination No primary data will be collected so formal ethical approval is not required. Findings will be disseminated through peer-reviewed publications, presented at international conferences and on social media.PROSPERO registration number PROSPERO CRD42024547535.